Optimization<U+0014>Theory and Practice - Forst, Wilhelm. (Springer Undergraduate Texts in Mathematics and Technology, 2010)
Optimization is an important field in its own right but also plays a central role in numerous applied sciences, including operations research, management science, economics, finance, and engineering. Optimization <U+0014> Theory and Practice offers a modern and well-balanced presentation of various optimization techniques and their applications. The book's clear structure, sound theoretical basics complemented by insightful illustrations and instructive examples, makes it an ideal introductory textbook and provides the reader with a comprehensive foundation in one of the most fascinating and useful branches of mathematics. Notable features include: Detailed explanations of theoretic results accompanied by supporting algorithms and exercises, often supplemented by helpful hints or MATLABʼ/MAPLEʼ code fragments; an overview of the MATLABʼ Optimization Toolbox and demonstrations of its uses with selected examples; accessibility to readers with a knowledge of multi-dimensional calculus, linear algebra, and basic numerical methods. Written at an introductory level, this book is intended for advanced undergraduates and graduate students, but may also be used as a reference by academics and professionals in mathematics and the applied sciences.